High Pressure Conduit: A Good Alternative to the Air Compressors Used in the Flotation Process - Sekerci, Kursat; Tuna, M. Cihat (Springer Heidelberg, 2021)
Flotation is used in various fields ranging from wastewater treatment to ore processing in mining. Flotation is largely based on aeration and oxygen transfer. By using water engineering principles, a significant amount of air bubbles can be transferred to the water in a short time. Today, conduits are the most important hydraulic structures used in aeration. The air taken from the atmosphere with the help of the air hole opening into the conduit is given to the water in bubbles. A large number of bubbles in the form of air flow accelerates the transfer of oxygen. As a result of these processes, flotation efficiency increases parallel to the aeration efficiency. In this study, a pressurized conduit integrated into the flotation cell and air bubbles are introduced into the system. In the pilot scale flotation system, the effect of various physical parameters such as conduit opening ratio, air intake hole length and diameter on flotation efficiency are investigated. Results indicate that this new system provides a very high amount of air bubbles to the flotation cell and the physical properties of the air intake hole has a significant effect on the amount of air entering the column (cell).
Keywords: Flotation; Hydraulic structures; Conduit; Aeration